Optimalisasi Pengadaan Koleksi untuk Mendukung Layanan Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Indah Putri Rahmadini; Marlini Marlini (KAMPUS AKADEMIK PUBLISING, 2026)
Collection acquisition is a fundamental aspect of library management as it directly affects the quality of services provided to users. The Provincial Archives and Library Office of West Sumatra, as a regional public library, is required to optimize its collection acquisition to meet diverse user information needs while considering limited resources. This study aims to examine the optimization of collection acquisition in supporting library services at the Provincial Archives and Library Office of West Sumatra. The research employs a qualitative approach using a descriptive method. Data were collected through in-depth interviews, observation, and documentation. An interview was conducted on December 16, 2025, with a key informant, namely the Head of the Collection Processing Team. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings indicate that collection acquisition is conducted through two main mechanisms: donations and purchases funded by the Regional Revenue and Expenditure Budget (APBD). The acquisition process begins with a user needs survey conducted through online and offline media, followed by an analysis of collection availability, user demand levels, and budget considerations before final acquisition decisions are made. The optimization of collection acquisition based on user needs and efficient budget management contributes to the provision of relevant, effective, and sustainable library services.